The hijab debate in the European countries: Perspective of women return migrants in Pakistan - Asia Ashfaq; Ahmed Usman; Muhammad Saud (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Choosing a dressing pattern is an individual decision shaped by multiple factors associated with one’s identity and sense of belonging. Based on their lived experiences, this study documents the perspective of women return migrants on the hijab in European context. In-depth interviews were conducted with the women presently living in the country of origin i.e. Pakistan. The women wearing the hijab faced multiple restrictions in their everyday life affairs. In a few countries, there were formal rules restricting the covering of head and face in the public sphere. The women experienced discrimination in employment opportunities because of the hijab as a dominant feature of their Muslim identity. Non-acceptance of the hijab is towards increase among the natives in European countries, who perceive that wearing the hijab in public spaces is leading their society towards conservative outlook. The study concludes that the hijab is one of the predominant factors that shape the decision of Muslim women residing in the Europe to return back to their country of origin.